De escola paroquial a escola pública: o significado da escola no desenvolvimento de Sananduva/RS - Neubarth, Selina Maria Dal Moro (1985)
The school, a social institution a150 present in Sananduva/RS, is analised in terms of it5 insertion in the social economical context of two historical periods: from 1898 to 1926 and from 1927 to 1955. The importance of the institution to that region, throghout those two historical periods, involves different educational interests: those of the 5tate, th05e of the Catholic Church, plust the ones defended by the settlers. The different and alternate roles played by the educational process during these historical periods have changed according to which of those three mentioned agents represented the prevailing face at a given time. Firstly, at the beginning of the settlement process (1898-1927) the sehoo1 took the shape of the necessities of the church and the settlers . It was seen as a useful instrument to the preservation of the settlers religious and cultural traditions. In the thirties, though, it served the State. as well as the Church and the Settlers . It became the schoo1 'for all'. It was now characterized as 'State school'.